Stable Spondylolisthesis: Should Management Change Based on Presence of Facet Cysts?. Issue 4 (May 2019) - Chugh, Arunit J.S.; Alonso, Fernando; Moore, Ryan; Cox, Efrem; Eubanks, Jason
Abstract : Study Design: This is a retrospective cohort review. Objective: To determine whether a correlation exists between facet cysts and lumbar instability. Summary of Background Data: Lumbar facet cysts are common degenerative entities observed in patients with low-grade spondylolisthesis at a rate of 10%–50%. Surgical management with partial facetectomy with or without fusion remains controversial. Methods: Review of 86 patients with lumbar degenerative spondylolisthesis is performed. Preoperative magnetic resonance imagings were reviewed for the presence of lumbar facet cysts and Facet Fluid Indices (FFI)—calculated as the ratio of facet fluid width to facet width. Instability was defined as a difference of >3 mm in vertebral displacement between flexion and extension radiographs. T tests and the Pearson correlation analyses were used to determine statistical significance. Results: In total, 26 patients had unstable and 60 had stable spondylolisthesis. Facet cysts were present at an overall prevalence of 30.1%—in 10/26 patients in the unstable group and in 18/60 patients in the stable group ( P >0.05). The average FFIs for the unstable and stable groups were 0.13 and 0.09, respectively ( P >0.05). FFI in patients with facet cysts was significantly higher than those without ( P <0.05). In addition, the group with facet cysts had a significantly higher proportion of patients with FF effusions >3 mm. Conclusions: Lack of correlation with instability hints that the presence of facet cysts may not indicate instability in lumbar degenerative spondylolisthesis. Therefore, presence of facet cysts in static magnetic resonance imaging revealing spondylolisthesis should not preclude the physician from performing dynamic films to evaluate for instability. Significantly higher FFI in patients with facet cysts reaffirms the degenerative pathophysiology involved in their formation. Although this is not an outcomes study, it does spark interest into whether patients with stable spondylolisthesis and concurrent facet cysts are suitable for partial facetectomy alone with fusion.